MODALITAS BELAJAR MAHASISWA PRODI PAI STAI DARUSSALAM LAMPUNG DITINJAU DARI GAYA BELAJAR - Laila Nursafitri; Nur Indah Sari; Taman Firdaus (LP2M IAI Muhammadiyah Bima, 2022)
Learning modality is a key to success in learning. Therefore, it is important to understand it so that effective learning can be carried out. This study aims to identify the learning modalities of the PAI STAI Darussalam Lampung students based on learning styles. This study uses descriptive research methods. The research sample was 35 students from the Islamic Religious Education study program (PAI). Using simple random sampling technique in sampling. Data was collected using a VARK (Visual, Aural, Read, Kinesthetic) questionnaire. Data analysis is presented in percentage. The results showed that the students of the Islamic Education Study Program (PAI) STAI Darussalam Lampung had several combinations of learning styles. The learning styles consist of 74.28% VARK (Visual – Aural – Read – Kinsesthetic), 2.85% VRK (Visual – Read –Kinsesthetic) combination, 5.71% VAK (Visual – Aural-Kinsesthetic) combination, the combination of ARK (Aural – Read –Kinsesthetic) was 5.71%, the combination of AK (Aural – Kinsesthetic) was 5.71%, and the combination of VK (Visual – Kinsesthetic) was 5.71%. The discussion of this study recommends learning that is suitable for students' learning modalities where they tend to have more than one type of learning style.